Four Switch Buck/Boost Converter for DC Microgrid Applications - Schulz, Matthias; Schleippmann, Nico; Gosses, Kilian; Wunder, Bernd; März, Martin (2020 EPE ECCE Europe, 2020)
A bidirectional non-isolated DC-DC converter with novel modulation scheme is used for connecting different devices with a voltage of up to 60 V in stand-alone or parallel connection to a droop-controlled DC microgrid. A prototype with a maximum power of 300 W and a peak efficiency of more than 97% is presented and analyzed.
Keywords: Microgrid; DC grid; Converter circuit; Batteries; Photovoltaic

Four Switch Buck/Boost Converter to Handle Bidirectional Power Flow in DC Subgrids - Schulz, Matthias; Schleippmann, Nico; Gosses, Kilian; Chacon, Raphael; Wunder, Bernd (2020 PCIM, 2020)
A non-isolated DC-DC converter is used for connecting different devices with a supply voltage of up to 60 V. Stand-alone operation is possible as well as using the communication interface of the converter to work in single or parallel configuration and to handle the bidirectional power flow in DC subgrids. Therefore, different voltage droop control characteristics are used. Constant current and constant voltage operation is implemented over the full voltage range for battery systems. A maximum power point tracking (MPPT) algorithm enables the connection of different photovoltaic panels. Experimental results based on a prototype with a maximum power of 300 W and a peak efficiency of 97% verify the validity.<br
Keywords: Buck/Boost converter; Bidirectional power flow; DC subgrids